Development of Phonological Constancy - Best, Catherine T.; Tyler, Michael D.; Gooding, Tiffany N.; Orlando, Corey B.; Quann, Chelsea A. (Psychological Science, 2009)
Efficient word recognition depends on detecting critical phonetic differences among similar-sounding words, or sensitivity to phonological distinctiveness, an ability evident at 19 months of age but unreliable at 14 to 15 months of age. However, little is known about phonological constancy, the equally crucial ability to recognize a word's identity across natural phonetic variations, such as those in cross-dialect pronunciation differences. We show that 15- and 19-month-old children recognize familiar words spoken in their native dialect, but that only the older children recognize familiar words in a dissimilar nonnative dialect, providing evidence for emergence of phonological constancy by 19 months. These results are compatible with a perceptual-attunement account of developmental change in early word recognition, but not with statistical-learning or phonological accounts. Thus, the complementary skills of phonological constancy and distinctiveness both appear at around 19 months of age, together providing the child with a fundamental insight that permits rapid vocabulary growth and later reading acquisition.